Audiovisual Translation, Multilingual Desire, and the Construction of the Intersectional Gay Male Body - Villanueva-Jordán, Iván (2023)
This study focuses on the HBO series Looking, whose two seasons and film make up a critical telecinematic artifact that reveals how authorial vision integrates ideologies on class, race, and desire that are identifiable in visual modes and language use—particularly multilingual dialogues. The analysis begins with the assumption that Looking is a relevant case of complex television and centers on the narrative structure of the series and the way that language, translation, and visual semiotic resources interact in the construction of a gay Latino character in the source version of the series and two Spanish dubbed versions—one for Latin America and the other for Spain. The findings reveal that Looking, as a televisual and aesthetic artifact, proposes a post-gay discourse of homoerotic relationships while also constructing racialized objects of desire, particularly the Latinx (male) body. A comparative linguistic analysis shows that both the dubbed versions highlight the boundaries of the so-called globalized gay identity. The data gathered demonstrate that the representation of ethnic, racial, and erotic difference changes according to the language system used. Moreover, new interactions between dubbed dialogues and visual resources result in a greater degree of semiotic layering of ideological discourses throughout the series.